Modified Dixon sequential method to determine the effective dose of alfentanil compounded with propofol for day-case hysteroscopy - Chenyang Xu; Rui Peng; Xiali Qian; Shanwu Feng; Hongmei Yuan (SAGE Publishing, 2023)
Background: Propofol combined with alfentanil is suitable for intravenous anesthesia for day-case hysteroscopy. Objective: To investigate the median effective dose (ED 50 ) and 95% effective dose (ED 95 ) of alfentanil compounded with propofol for day-case hysteroscopy. Design: In all, 29 patients who volunteered for painless hysteroscopy in 2022 were recruited. 1.5 mg/kg propofol was given as a sedative to all patients. The trial was conducted using the modified Dixon sequential method, with an initial dose of 10 μg/kg of alfentanil, and the subject's alfentanil dose depended on whether the prior hysteroscopy had failed, which was defined as inadequate cervical dilatation and hysteroscope placement with the patient exhibiting body movement, frowning, or a MOAA/S score >1. If the hysteroscopy failed (i.e. a positive response), the subsequent subject's alfentanil dosage was raised, and conversely (i.e. a negative response), the dose was decreased, with the adjacent dose ratio always being 1:1.2. The formal test begins with the first crossover wave and lasts until seven crossover waves materialize. Methods: The probit method was used to calculate the ED 50 , ED 95 , and corresponding 95% confidence intervals (CIs) of alfentanil compounded with propofol for hysteroscopy. Results: The ED 50 and ED 95 of alfentanil combined with propofol for day-case hysteroscopy were 5.701 (95% CI: 3.841-7.069) μg/kg and 8.817 (95% CI: 7.307-20.868) μg/kg, respectively. Conclusion: Alfentanil at 8.817 μg/kg in conjunction with propofol is a successful and safe approach for day-case painless hysteroscopy. Trial registration: The trial registry name: Modified sequential method to determine the half-effective dose of alfentanil compounded with propofol for ambulatory hysteroscopy. The URL of registration is https://www.chictr.org.cn/showproj.html?proj=171786 , where the full trial protocol can be accessed. Registration number: ChiCTR2200061619.